2009
DOI: 10.1002/mar.20291
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of Chinese consumer values, consumption values, life satisfaction, and consumption behaviors

Abstract: The primary objective of this study was to investigate how the changing value systems of modern Chinese consumers affect their consumption behaviors and life satisfaction through the mediating variables of consumption values. The results of the multivariate data analysis show that three out of four types of consumer values (i.e., functional, emotional, and social) were positively related to foreign brand purchasing. Among all accepted relationships, the one between collectivism and functional value was the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 33 publications
8
105
0
6
Order By: Relevance
“…Table 7.3 shows the data on buying behaviour. The data shows the presence of repeat purchases during the year for Chinese consumers, like in most industrialized countries (see Xiao and Kim, 2009). It also denotes the strong centrality of mothers in the purchasing process (see Sin and Yau, 2004), which is a result that differentiates China from other countries of the so-called 'Old World', where the role of the family (especially grandparents) has a greater economic and social value.…”
Section: Sample and Descriptive Statisticsmentioning
confidence: 91%
“…Table 7.3 shows the data on buying behaviour. The data shows the presence of repeat purchases during the year for Chinese consumers, like in most industrialized countries (see Xiao and Kim, 2009). It also denotes the strong centrality of mothers in the purchasing process (see Sin and Yau, 2004), which is a result that differentiates China from other countries of the so-called 'Old World', where the role of the family (especially grandparents) has a greater economic and social value.…”
Section: Sample and Descriptive Statisticsmentioning
confidence: 91%
“…It is generally associated with features such as performance reliability, durableness, and functionality (D'Souza et al 2007). In short, it is related to a product or service's quality and price benefit (Xiao and Kim, 2009). In this sense, it can be classified as functional price value and functional quality value.…”
Section: Consumption Valuesmentioning
confidence: 99%
“…They found that collectivistic individuals created fewer ideas that depart from the pre-existing solutions than individualistic individuals. Moreover, in many Asian cultures, people are encouraged to suppress their hedonic desires (Kacen and Lee, 2002) and to pursue utilitarian benefits such as durability [e.g., Xiao and Kim (2009)]. Thus, consumers with a higher level of relational orientation may perceive less utility from the unique product, experience less enjoyment, and feel less absorbed in the shopping experience with apparel mass customisation compared with consumers who have a lower level of relational orientation.…”
Section: Relational Orientationmentioning
confidence: 99%